G402(P) A review of our local experiences with the supportt return to training policy: is it working in practice?. (25th October 2020) - Keane, M; Ogden, S; Wade, L; Jobling, A; Mehta, F
Abstract : Background: Health Education England has introduced a Supported Return to Training (SuppoRRT) policy advocating additional provision for returning trainees. This echoes feedback previously presented from local trainees demonstrating need for increased training resources. Following the introduction of a local RTT policy in 2018 we aimed to evaluate uptake to inform further resource provision. Methods: Online questionnaire to all educational supervisors and all trainees taking time-out-of-training across deanery. Results: Currently, we have responses from 15 educational-supervisors and 11 trainees. 82% trainees and 87% educational-supervisors were aware of the policy; most trainees learnt about it during time-out. This was reflected by the 64% of trainees who did not arrange a pre-absence meeting or make any advance plans for anticipated needs on returning. Many limitations were discussed regarding keeping-in-touch (KIT) days. Post-absence-review meetings were reported by 44% of trainees and 86% of educational supervisors. Supportive measures were arranged by 66% of trainees to aid return. A period of supervised-on-calls on return was reported by 86% of supervisors but no trainees, with 75% deeming it unnecessary. 78% of trainees and 43% of supervisors did not report confirming-readiness-to-practice meetings before usual on-calls resumed. 57% of supervisors were unaware of SuppoRRT-funding available to meet specific training needs. Overall 91% trainees and 87% of educational-supervisors found that the RTT policy was working well, either partly (64% and 47%) or mostly (27% and 40%). Both trainees and supervisors felt that the policy improved trainee wellbeing (57% and 57%), trainee development (42% and 21%) and patient safety (71% and 64%). Comparing responses from our previous survey, following implementation of the policy there was a reduction in trainees feeling 'unnecessarily exposed' from 76% to 27%. Conclusion: Overall there are positive responses on the new RTT policy, although the method introduces inherent bias. However, some resources are not fully utilised such as KIT days and a 'supervised-on-call' period. Increased awareness of the policy and implementation of RTT meetings is required alongside increasing accessibility of training-resources to enable appropriate tailored support for returning-trainees.